The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3989/redc.2011.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Características y disparidades entre sub-especialidades: un estudio de caso con grupos de Biotecnología

Abstract: Resumen: El objetivo de este trabajo es el estudio de las características y disparidades entre las sub-especialidades existentes dentro de categorías interdisciplinares, planteando la necesidad de identifi car y evaluar por separado cada una de ellas. Se analizan los años 2003-2006, a través de las bases de datos del Web of Science (WoS), y se exploran las posibles diferencias entre grupos de investigación de Biotecnología de la Comunidad de Madrid según su perfi l de especialización. Esta región española es l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…We not only offer an overview of the research carried out in this context, but we also study dissimilarities with non-networking centres and differences between disciplines. We can determine that these Spanish structures have similar characteristics to those of other countries, and particular features of each research topic explain the differences found, as it was stated in a previous study (Morillo & Aparicio, 2011). The HJ-Biplot enables us to study these variances concluding that this kind of association produces synergies and outputs with higher levels of collaboration and impact.…”
Section: Discussionmentioning
confidence: 78%
“…We not only offer an overview of the research carried out in this context, but we also study dissimilarities with non-networking centres and differences between disciplines. We can determine that these Spanish structures have similar characteristics to those of other countries, and particular features of each research topic explain the differences found, as it was stated in a previous study (Morillo & Aparicio, 2011). The HJ-Biplot enables us to study these variances concluding that this kind of association produces synergies and outputs with higher levels of collaboration and impact.…”
Section: Discussionmentioning
confidence: 78%